2013
DOI: 10.1021/nl304426y
|View full text |Cite
|
Sign up to set email alerts
|

Aspect Ratio Dependence of Auger Recombination and Carrier Multiplication in PbSe Nanorods

Abstract: Nanomaterials with efficient carrier multiplication (CM), that is, generation of multiple electron-hole pairs by single photons, have been the object of intense scientific interest as potential enablers of high efficiency generation-III photovoltaics. In this work, we explore nanocrystal shape control as a means for enhancing CM. Specifically, we investigate the influence of aspect ratio (ρ) of PbSe nanorods (NRs) on both CM and the inverse of this process, Auger recombination. We observe that Auger lifetimes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
195
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(217 citation statements)
references
References 57 publications
20
195
2
Order By: Relevance
“…In the case of PbSe rods with L = 8a 0 (4.9 nm) we predict a decrease of the CM critical energy from ∼ 3.0E g to ∼ 2.25E g for an increase of σ from 1 to 4, in good agreement with the experimental results of Cunningham et al 32 who observed a reduction of E onset from 2.9 to 2.33 for aspect ratios increasing from 1 to 4-5 in nanorods with typical diameters of 4.4 nm. Furthermore, our predicted size independence for σ min is consistent with the recent findings of a diameter-independent maximum for the CM yields observed at aspect ratios of about 8 35 . Indeed, according to our results, the CM threshold does not exhibit any further decrease (hence the CM efficiency is not expected to further increase) with increasing values of σ beyond about 9 (which value is also in fair agreement with experiment).…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…In the case of PbSe rods with L = 8a 0 (4.9 nm) we predict a decrease of the CM critical energy from ∼ 3.0E g to ∼ 2.25E g for an increase of σ from 1 to 4, in good agreement with the experimental results of Cunningham et al 32 who observed a reduction of E onset from 2.9 to 2.33 for aspect ratios increasing from 1 to 4-5 in nanorods with typical diameters of 4.4 nm. Furthermore, our predicted size independence for σ min is consistent with the recent findings of a diameter-independent maximum for the CM yields observed at aspect ratios of about 8 35 . Indeed, according to our results, the CM threshold does not exhibit any further decrease (hence the CM efficiency is not expected to further increase) with increasing values of σ beyond about 9 (which value is also in fair agreement with experiment).…”
Section: Methodssupporting
confidence: 91%
“…This could lead to more highly efficient devices sitting on the same substrate, and therefore harnessing even more energy from sunlight. Furthermore, although experimentally the CM onset has been shown to be independent of the NC size, for spherical NCs of a specific material 14,30 , it has recently been found to depend on the NC shape [31][32][33][34][35] . Therefore further theoretical and experimental work is required on this subject 36 to shed light on these experimental findings.…”
Section: Introductionmentioning
confidence: 99%
“…10 An efficiency of 130% for the generation of an e-h pair by an absorbed photon has been reported for bulk silicon irradiated with ultraviolet light. 8 CM was found to be considerably enhanced in spatially confined materials, such as graphene 11 and lead sulfide nanosheets 12 (two-dimensional confinement), carbon nanotubes 13 and lead selenide nanorods 14,15 (one-dimensional confinement) and in quantum dots (zero-dimensional confinement). 16 In the latter case, CM was studied for quantum dots in a colloidal dispersion or embedded in a solid matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in QDs, recent spectroscopic findings are indicative of MEG thresholds MEG th ( ) E being closer to the energy conservation limit (2E g ) than in the parental bulk material [30,31,45,46]. In these reports, the authors also find a close correlation between MEG th E and the MEG efficiency (η MEG ).…”
Section: Enhancing CM In Qdsmentioning
confidence: 87%
“…nanorods) have shown improved MEG efficiencies over spherical QDs not only on the single particle level [45,46], but also in devices [27]. This has mainly been attributed to two effects: first, the stronger Coulomb matrix element in nanorods, which has been shown to increase MEG without altering the reverse process (i.e.…”
Section: Tuning the Shape Of The Qdmentioning
confidence: 99%